The Vietnam Report: National Landscape, Current Challenges and Opportunities for Growth - Institute for Societal Leadership, (Institutional Knowledge at Singapore Management University, 2015)
Although most of Southeast Asia is home to religions and cultures carrying signiﬁcant Indic inﬂuence, Vietnam alone is the mainland’s only Sinicised culture. Chinese emperors directly ruled northern Vietnam for most of the period spanning 111 BCE to 938 CE. The next eight hundred years saw a series of independent Vietnamese kingdoms administered by Chinese-style mandarins gradually extend control over and supplant the Indic Champa civilisation to the south—even as French incursions began chipping away at Vietnamese territory as early as 1858.